PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS SOFTWARE MACROMEDIA FLASH TERHADAP HASIL BELAJAR MESIN KONVERSI ENERGI DI SMK NEGERI 1 BALIKPAPAN - Malik, Abdul; munoto, munoto; cholik, mochamad (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
ABSTRACT This study aims : (1) to examine and analyze the differences in energy conversion machine learning outcomes between students who studied with the use of instructional media macromedia flash with students who study with the use of student worksheets; (2) to examine and analyze the differences in energy conversion machine learning outcomes between students who have learning motivation high and low learning motivation; and (3) to examine and analyze the interaction between the use of instructional media by using macromedia flash, worksheets, and motivation toward learning outcomes of energy conversion machines.. This research is an experimental study using a Non-Random Pre-test and Post-test Control Group with the use of factorial design study model of 2x2 design, population of tenth grade students of SMK Negeri 1 TKR in Balikpapan. Data collection techniques with methods of testing for learning outcomes and methods for learning motivation questionnaire. Analysis of the data in SPSS using two-sample t-test and ANOVA, two independent parts, test requirements normality using Kolmogorov-Smirnov test, homogeneity test requirements using the Levene test. The results of the study: (1) the influence of the energy conversion machine learning outcomes between students who learn to use macromedia flash media with students who are learning to use the media student worksheets obtained F value = 0.039 to 0.843 significant. Because significant < 0.05 then H0 is rejected and H1 accepted, so in this study the energy conversion machine learning results in students learning with macromedia flash media is significantly higher than students who studied the learning media LKS; (2) differences in learning outcomes between students' energy conversion machine which has a high learning motivation and low learning motivation obtained results of F = 0.570 obtained results with significant 0,453. Because significant < 0.05 then H0 is rejected and H1 accepted as a result of energy conversion of learning material to students who have a high learning motivation is significantly higher than students who have low motivation; (3) to examine and analyze the interaction between the use of instructional media by using macromedia flash, worksheets, and motivation toward learning outcomes of energy conversion machines. is obtained F value = 0.128 to 0.722 significant . Because significant < 0.05 then Ho is rejected and H1 accepted in this study so there is an interaction between the use of instructional media by using macromedia flash, worksheets, and motivation toward learning outcomes of energy conversion machines. Keywords : Macromedia flash , student worksheets, motivation to learn, and learning outcomes